2012
DOI: 10.1111/j.1447-0756.2012.02039.x
|View full text |Cite
|
Sign up to set email alerts
|

How accurate is intraoperative frozen section in the diagnosis of ovarian tumors?

Abstract: Frozen section diagnosis is of high quality at our center with a few exceptions in borderline category. The numbers of sections examined have a statistically significant influence on the accuracy of frozen section of ovarian masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…The diagnostic value of frozen section (accuracy, sensitivity, specificity, negative predictive value, positive predictive value) was summarized and presented in Table 5. Our data was compared to previous literature in other countries (Malipatil et al, 2013;Ayhan et al, 2016;Hashmi et al, 2016;Arshad et al, 2018). All data from previous Thai studies (Boriboonhirunsarn et al, 2004;Tangjitgamol et al, 2004;Wootipoom et al, 2006;Wasinghon et al, 2008;Suprasert et al, 2008) were summarized and presented as summary data in Table 5.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…The diagnostic value of frozen section (accuracy, sensitivity, specificity, negative predictive value, positive predictive value) was summarized and presented in Table 5. Our data was compared to previous literature in other countries (Malipatil et al, 2013;Ayhan et al, 2016;Hashmi et al, 2016;Arshad et al, 2018). All data from previous Thai studies (Boriboonhirunsarn et al, 2004;Tangjitgamol et al, 2004;Wootipoom et al, 2006;Wasinghon et al, 2008;Suprasert et al, 2008) were summarized and presented as summary data in Table 5.…”
Section: Resultsmentioning
confidence: 73%
“…PPV of his study was equal to the PPV of our study when the frozen section results reported benign tumors. Reports from India, Bangladesh, and Malaysia showed similar PPV from frozen sections with suspected benign condition (Malipatil et al, 2013;Hashmi et al, 2016;Arshad et al, 2018). In the current study, there were 100 benign ovarian tumor cases from the frozen section reports.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…A diagnostic tool which helps to identify various ovarian lesions with high degree of accuracy will help the surgeon to choose appropriate operating procedure [2,3]. Preoperative diagnostic modalities include serum tumor marker level estimation and imaging.…”
Section: Introductionmentioning
confidence: 99%